Memory Impairment in Transgenic Alzheimer Mice Requires Cellular Prion Protein - Gimbel, David A. (Society for Neuroscience, 2010)
Soluble oligomers of the amyloid-β (Aβ) peptide are thought to play a key role in the pathophysiology of Alzheimer's disease (AD). Recently, we reported that synthetic Aβ oligomers bind to cellular prion protein (PrP(C)) and that this interaction is required for suppression of synaptic plasticity in hippocampal slices by oligomeric Aβ peptide. We hypothesized that PrP(C) is essential for the ability of brain-derived Aβ to suppress cognitive function. Here, we crossed familial AD transgenes encoding APPswe and PSen1ΔE9 into Prnp−/− mice to examine the necessity of PrP(C) for AD-related phenotypes. Neither APP expression nor Aβ level is altered by PrP(C) absence in this transgenic AD model, and astrogliosis is unchanged. However, deletion of PrP(C) expression rescues 5-HT axonal degeneration, loss of synaptic markers, and early death in APPswe/PSen1ΔE9 transgenic mice. The AD transgenic mice with intact PrP(C) expression exhibit deficits in spatial learning and memory. Mice lacking PrP(C), but containing Aβ plaque derived from APPswe/PSen1ΔE9 transgenes, show no detectable impairment of spatial learning and memory. Thus, deletion of PrP(C) expression dissociates Aβ accumulation from behavioral impairment in these AD mice, with the cognitive deficits selectively requiring PrP(C).